Mathematical model of vacuum freeze-drying in the secondary drying - Li, Hua; Li, Lihua; Jiao, Xingli; Qin, Xueli (JOURNAL OF ADVANCES IN CHEMISTRY, 2007)
The freeze-drying process is a complex heat and mass transfer process virtually. The drying process of freeze-drying is not only the key stage which decides the success of freeze-drying, but also the most difficult stage to control. There are lots of papers about heat and mass transfer in vacuum freeze drying at home and abroad. The present status of research on heat and mass transfer during vacuum freeze drying in the secondary drying is summed up and analyzed, and the trend of research in this field is discussed in this paper.